2006
DOI: 10.1111/j.1749-4486.2006.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

How we do it: Coblation tonsillectomy complication rates from a single ENT department compared with the National Prospective Tonsillectomy Audit

Abstract: Coblation tonsillectomy is a relatively new technique, the results of which need auditing within practising units, to justify its continued usage. * The National Prospective Tonsillectomy Audit provides an excellent source of data for individual units to compare their results to. * This retrospective audit of 391 coblation tonsillectomies shows that our units haemorrhage and return to theatre rates are similar to the National rates for cold steel & ties data. * Resolution of training issues and patient selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
(1 reference statement)
1
9
0
Order By: Relevance
“…In contrast, multiple other studies have concluded that the bleeding rate following Coblation tonsillectomy was not statistically different than with non‐Coblation procedures 31–34. The National Prospective Tonsillectomy Audit (NPTA) of Great Britain included 13,554 patients, of whom 60% were pediatric; in this review, 684 of the procedures were performed using the Coblation technique.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, multiple other studies have concluded that the bleeding rate following Coblation tonsillectomy was not statistically different than with non‐Coblation procedures 31–34. The National Prospective Tonsillectomy Audit (NPTA) of Great Britain included 13,554 patients, of whom 60% were pediatric; in this review, 684 of the procedures were performed using the Coblation technique.…”
Section: Discussionmentioning
confidence: 92%
“…A number of articles have suggested an increased risk of haemorrhage in patients undergoing coblation tonsillectomy 6,11–13 . However, other investigators have not found this to be the case 14,15 . Belloso et al 16 showed a lower incidence of haemorrhage in the largest single study to date (2.25% in the coblation group versus 6.19% in the control group).…”
Section: Discussionmentioning
confidence: 99%
“…6,[11][12][13] However, other investigators have not found this to be the case. 14,15 Belloso et al 16 showed a lower incidence of haemorrhage in the largest single study to date (2.25% in the coblation group versus 6.19% in the control group). The present study was not intended to address this question.…”
Section: Secondary Haemorrhagesmentioning
confidence: 94%
“…The ionised helium is used to dissect and coagulate the tissues [9]. Clark et al [11] report a secondary haemorrhage rate of 1.5 % for coblation with no patients returning to theatre for controlling haemorrhage. They report that patients were discharged on oral antibiotics after 24 h of intravenous antibiotics when they presented with bleeding.…”
Section: Discussionmentioning
confidence: 99%